Using Ishikawa Diagram to Analysis Causes of Survival of Microorganism in Steamed Ground Poultry Meat as Ingredient of the Blenderized Formula for Tube Feeding: A Case Study at Phatthalung Hospital - Purinthrapibal , Pakamart; Choosuwan, Atittiya; Sripakdee, Supapan; Kongtongsang, Somsook; Naunthong, Rawiwan; Khunsri, Supatsara; Phatchuay, Natthatida; Kaewtong, Apisara; Kongkanon, Phatsakorn (Recent Science and Technology, 2020)
Phattalung hospital with 445 patient beds had 22% of patients for tube feeding. The tube feeding products daily prepared from nutritional section had microbial quality within acceptable limits. But in September 2018, the internal audit by consumer protection section of Phatthalung hospital reported that Eschericia coli exceeded the acceptable limit in steamed ground poultry meat used as blenderized formula of breakfast tube feeding. Therefore, this research started to analyze and determine the cause of problems using Ishikawa diagrams. The analysis results showed four main factors that affected remaining Eschericia coli in steamed ground poultry meat. Risk identification stage showed that the method factor had the highest risk followed by raw material, staff and equipment, respectively. Improving the method by reducing the amount of fresh grounded poultry meat per steaming tray and controlling the steaming time that core temperature of steamed ground poultry should not be lower than 90 ๐C. Risk from raw material was prevented by only using Q mark fresh ground poultry meat. Sampling of staff and equipment showed microbial quality within acceptable limits. Therefore, Ishikawa diagram is an appropriate tool for identifying the root cause of a problem and leading to a guideline to solve the problem.